2010
DOI: 10.1111/j.1398-9995.2009.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and adult asthma: population‐based case–control study

Abstract: Overall there were no clear relations between dietary patterns and adult asthma; associations in nonsupplement users and whites require confirmation. The finding for chronic bronchitis was unexpected and also requires replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 31 publications
4
60
1
Order By: Relevance
“…12,13 Soft drinks are an important component of the Western lifestyle and diet. The intake of soft drinks in Australia has grown rapidly from around 47.3 L per person per year in 1969 to 113 L per person (both children and adults) in 1999.…”
Section: Summary At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Soft drinks are an important component of the Western lifestyle and diet. The intake of soft drinks in Australia has grown rapidly from around 47.3 L per person per year in 1969 to 113 L per person (both children and adults) in 1999.…”
Section: Summary At a Glancementioning
confidence: 99%
“…9 Since 2007, a few reports have been published on the association between dietary patterns and asthma/COPD. [10][11][12][13][14][15][16] Among these studies,…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion that a higher intake of antioxidants might promote the development of allergic disease is certainly contrary to the prevailing antioxidant paradigm [88]. Earlier studies showed that frequent consumption of fruit and raw vegetables reduced the risk of asthmatic symptoms like wheezing [101].…”
Section: Antioxidants Are a Two-edged Swordmentioning
confidence: 60%
“…This conclusion is further strengthened by the fact that cooking of such foods is able to prevent allergic responses as antioxidant compounds and vitamins are destroyed. A higher intake of β-carotene was also reported to be associated with a higher prevalence of rhinitis [88] and hay fever [89]. Reported side effects of food preservatives like sodium sulfite and benzoate comprise the possibility of allergic reactions.…”
Section: In Vivo Correlatesmentioning
confidence: 99%
“…9,10,12 Others have inconclusive results as far as the role of dietary pattern in asthma prevention and treatment is concerned. 14,16 Although there have been numerous studies more population based study are required to established the association asthma, allergy and diet. However on a larger perspective, we can look at the diets of people and its effect on asthma by dividing them into lacto ovo vegetarian and non-vegetarians.…”
Section: Introductionmentioning
confidence: 99%